2020
DOI: 10.3390/s20102904
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Enhance the Packing Density of Buckypaper for Superior Piezoresistive Sensor Characteristics

Abstract: Transforming individual carbon nanotubes (CNTs) into bulk form is necessary for the utilization of the extraordinary properties of CNTs in sensor applications. Individual CNTs are randomly arranged when transformed into the bulk structure in the form of buckypaper. The random arrangement has many pores among individual CNTs, which can be treated as gaps or defects contributing to the degradation of CNT properties in the bulk form. A novel technique of filling these gaps is successfully developed in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The results showed that the starting material (Figure 2a) contained interweaved SWCNTs and their bundles, which were distributed therein without any degree of anisotropy. The material appeared porous, as expected for SWCNT networks [33]. Importantly, only negligible amounts of contamination such as amorphous carbon or metallic species could be discerned.…”
Section: Resultssupporting
confidence: 54%
“…The results showed that the starting material (Figure 2a) contained interweaved SWCNTs and their bundles, which were distributed therein without any degree of anisotropy. The material appeared porous, as expected for SWCNT networks [33]. Importantly, only negligible amounts of contamination such as amorphous carbon or metallic species could be discerned.…”
Section: Resultssupporting
confidence: 54%
“…Applications of Simulink are very broad and include digital signal processing, the analysis of electrical circuits and the design and testing of devices and control systems. The analysis of systems using simulation methods can significantly reduce the time and costs needed to prepare or improve control system prototypes [ 20 ].…”
Section: Methods Of Experimentsmentioning
confidence: 99%
“…However, the assistance was unnecessary, because after landing it turned out that the signal about the existence of fire in the engine turned out to be false. The probable cause of the failure of the fire detection system was a faulty sensor [ 20 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…48 Sakurai et al fabricated CNT BPs from CNT forests of varying heights, and the tensile strength of BPs with heights from 350 to 1500 mm ranged from 27 to 52 MPa. 46 49 Although improving the entanglement and increasing the CNT size have been proved to be effective ways to improve the mechanical properties of films, fabricated materials are still much weaker than the individual CNTs, which will limit their potential applications. The main reason is that the traditional BP is composed of a certain number of short CNTs intertwined with each other and inter-tube sliding between CNTs always happens, which can impair the tensile strength of the BP.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 So far, great efforts have been made to enhance the mechanical properties and there are mainly two typical methods: improving the entanglement [43][44][45] and increasing the CNT size. [46][47][48][49][50] For improving the entanglement, heterogeneous micro/nanoadditives 51,52 and strong covalent bonds 45,53,54 between CNTs have been introduced to overcome the weak vdW interactions. Rani et al studied the influence of a surfactant on the mechanical properties of a BP and reported a 104% improvement in its tensile strength.…”
Section: Introductionmentioning
confidence: 99%